Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12862-023-02144-8
|View full text |Cite
|
Sign up to set email alerts
|

History of the terrestrial isopod genus Ligidium in Japan based on phylogeographic analysis

Wakana Harigai,
Aya Saito,
Chika Zemmoto
et al.

Abstract: Background Phylogeographical approaches explain the genetic diversity of local organisms in the context of their geological and geographic environments. Thus, genetic diversity can be a proxy for geological history. Here we propose a genus of woodland isopod, Ligidium, as a marker of geological history in relation to orogeny and the Quaternary glacial cycle. Results Mitochondrial analysis of 721 individuals from 97 sites across Japan revealed phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(92 reference statements)
1
1
0
Order By: Relevance
“…The authors suggest that the observed high genetic differentiation may result from strict ecological specialization to very humid soil habitats, causing strong geographic isolation in a relatively dry region such as the Eastern Mediterranean. However similar patterns have been found among temperate, subtropical and montane climates in regions of Japan (Harigai et al, 2020(Harigai et al, , 2023Yoshino & Kubota, 2022) and China, where several new species have been delimited with the help of molecular data (Li, 2017;Wang et al, 2022). Overall, this suggests that Ligidium species have limited dispersal capacities, favouring genetic lineage differentiation and eventually speciation, most likely by allopatric isolation coupled with ecological niche conservatism (Wiens, 2004).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The authors suggest that the observed high genetic differentiation may result from strict ecological specialization to very humid soil habitats, causing strong geographic isolation in a relatively dry region such as the Eastern Mediterranean. However similar patterns have been found among temperate, subtropical and montane climates in regions of Japan (Harigai et al, 2020(Harigai et al, , 2023Yoshino & Kubota, 2022) and China, where several new species have been delimited with the help of molecular data (Li, 2017;Wang et al, 2022). Overall, this suggests that Ligidium species have limited dispersal capacities, favouring genetic lineage differentiation and eventually speciation, most likely by allopatric isolation coupled with ecological niche conservatism (Wiens, 2004).…”
Section: Introductionsupporting
confidence: 62%
“…The genus Ligidium has proven to be more diverse than initially expected in several parts of the Holarctic, after the integration of dense sampling and molecular data (Harigai et al, 2023;Klossa-Kilia et al, 2006;Wang et al, 2022). Integrative taxonomic approaches have found the existence of truly cryptic Ligidium species, hardly diagnosable based on morphological characters (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%